An Inconvenient Truth: The Quandary of Dystopian Earth in Douglas Trumbull’s Silent Running and Richard Fleischer’s Soylent Green - D’cruz, Adrene Freeda (My University, 2012)
Ecocide, the widespread annihilation of nature, constitutes the principal theme of Douglas Trumbull’s Silent Running (1972) and Richard Fleischer’s Soylent Green (1973). Seeking recourse to one of the major film genres, namely, science fiction, these films emphatically disclose an inconvenient truth - the imminent extinction of the ecosystem. Set in a dystopian world, the films outline two futuristic probabilities: the sustenance of the last trace of bio-network only on spaceships in Silent Running and the overpopulated city haunted by the scarcity of natural resources in Soylent Green. In other words, while Silent Running strategically uncovers an already depleted biosphere, Soylent Green systematically examines the road to ecological perdition. Significantly, the cinematic space resorts to diverse techniques, including stills, close-up, voice-over, and music, to convey the petrifying reality that awaits humanity in the near future. Drawing the title from Davis Guggenheim’s An Inconvenient Truth, a documentary on global warming, this paper, in analyzing the environmental apocalypse in Silent Running and Soylent Green, seeks to reveal how the cinematography weaves an ecocentric discourse to promote the inevitable truth that ecosphere is intrinsic to human survival.
Keywords: Ecocide; Bio-network; Ecosphere